Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
Step-by-step explanation:
The given function is:
[tex]f(x) = \dfrac{x}{\sqrt{9+x^2}}[/tex]
Using the binomial series:
[tex]= x(9+x^2)^{-1/2} \\ \\ = x *9^{-1/2}(1+\dfrac{x^2}{9})^{-1/2} \\ \\ = \dfrac{x}{3}(1+ \dfrac{x^2}{9})^{-1/2}[/tex]
[tex]= \dfrac{x}{3} \sum \limits ^{\alpha }_{n=0}(^{-\frac{1}{2}}_n)(\dfrac{x^2}{9})^n[/tex]
[tex]\implies \dfrac{x}{3}\Bigg [ 1 + (-\dfrac{1}{2})*(\dfrac{x^2}{9})+ \dfrac{(-\dfrac{1}{2})(-\dfrac{1}{2}-1)}{2!}(\dfrac{x^2}{9}) ^2 + \dfrac{(-\dfrac{1}{2})(-\dfrac{1}{2}-1) (-\dfrac{1}{2}-2)}{3!} ) (\dfrac{x^2}{9}) ^3+ ... \Bigg ][/tex]
[tex]= \dfrac{x}{3}\Bigg [ 1 - \dfrac{x^2}{18}+ \dfrac{3}{5832}*\dfrac{x^4}{1}-\dfrac{15}{34992}x^6+... \Bigg ][/tex]
[tex]\mathbf{= \dfrac{x}{3}- \dfrac{x^3}{54}+ \dfrac{1}{5832}x^4 - \dfrac{5}{34992}x^7 + ...}[/tex]
To compute the radius of convergence:
[tex]f(x) = \dfrac{\lambda }{3} \sum \limits ^{\alpha }_{n=0} (1+\dfrac{x^2}{9})^{-1/2}[/tex]
[tex]f(x) = \dfrac{\lambda }{3} \sum \limits ^{\alpha }_{n=0} (^{-1/2} _n ) (\dfrac{x^2}{9})^n \\ \\ \implies \dfrac{\lambda }{3} \sum \limits ^{\alpha }_{n=0} (^{-1/2} _n ) (\dfrac{x^2}{9})^n \\ \\ \implies \sum \limits ^{\alpha}_{n=0} (^{-1/2} _n ) \dfrac{1}{3*9^n}*x^{2n} \\ \\ \implies \sum \limits ^{\alpha}_{n=0} (^{-1/2} _n ) \dfrac{1}{3^{2n+1}}*x^{2n}[/tex]
Suppose [tex]a_n = (^{-1/2}_{n})*\dfrac{1}{3^{2n+1}}*x^{2n}[/tex]
Then, rewriting the equation above as:
[tex]a_{n+1} = (^{-1/2}_{n+1})*\dfrac{1}{3^{2n+3}}*x^{2n+2}[/tex]
As such;
[tex]\lim_{n \to x} \Big| \dfrac{a_n+1}{a_n} \Big| = \lim_{n \to x} \Bigg | \dfrac{ (^{-1/2}_{n+1}) \dfrac{x^{2n+2}}{3^{2n+3}} }{(^{-1/2}_{n} )\dfrac{x^2}{3^{2n+1}}}} \Bigg |[/tex]
[tex]\implies \lim_{n \to \alpha} \Bigg | \dfrac{ (^{-1/2}_{n+1}) \dfrac{x^{2}}{3^{2}} }{(^{-1/2}_{_n} )} \Bigg |[/tex]
[tex]\implies \lim_{n \to \alpha} \Bigg | \dfrac{\dfrac{(-1/2)!}{(-1/2-n -1)!(n+1)!}*\dfrac{x^2}{9} }{ \dfrac{(-1/2!)}{(-1/2-n)!(n!)} } \Bigg| \\ \\ \\ \implies \lim_{n \to \alpha} \Bigg | \dfrac{(-1/2 -n)! (n!) }{(-1/2 -n-1)! (n+1)! } *\dfrac{x^2}{9} \Bigg| \\ \\ \\ \implies \lim_{n \to \alpha} \Bigg | \dfrac{(-1/2 -n) (-1/2 -n-1)! \ n! }{(-1/2 -n-1)! (n+1) n! } *\dfrac{x^2}{9} \Bigg|[/tex]
[tex]\implies \lim_{n \to \alpha} \Bigg | \dfrac{(-1/2 -n)}{n+1 } *\dfrac{x^2}{9} \Bigg|[/tex]
[tex]\implies \lim_{n \to \alpha} \Bigg | \dfrac{n( -\dfrac{1}{2n -1 } ) }{n(1+\dfrac{1}{n}) } *\dfrac{x^2}{9} \Bigg| \\ \\ \\ \implies \Big| \dfrac{x^2}{9} \Big| \lim_{n \to \alpha} \Big | \dfrac{-\dfrac{1}{2n} -1}{1+ \dfrac{1}{n}} \Big| \\ \\ \implies | \dfrac{x^2}{9}| |\dfrac{0-1}{1}|[/tex]
[tex]\implies | \dfrac{x^2}{9}|[/tex]
However, the series converges if and only if:
[tex]| \dfrac{x^2}{9}| < 1[/tex]
∴
[tex]\dfrac{|x^2|}{9} < 1[/tex]
[tex]={|x^2|}< 9 \\ \\ ={|x|} < \sqrt{9} \\ \\ = \mathbf{{|x|} < 3}[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.